Automatic dose verification system for breast radiotherapy: Method validation, contour propagation and DVH parameters evaluation. (May 2022) - Baeza, Jose A.; Zegers, Catharina M.L.; de Groot, Nienke A.; Nijsten, Sebastiaan M.J.J.G.; Murrer, Lars H.P.; Verhoeven, Karolien; Boersma, Liesbeth; Verhaegen, Frank; van Elmpt, Wouter
Highlights: An automatic DVH-based dose verification system with contour propagation was developed. Thirty-one breast cancer patients were used to benchmark the dose verification system against the TPS. Strong agreement in DVH parameters were found between the dose verification system and the TPS. Uncertainties derived from the dose verification system, with and without automatic contour propagation, were quantified. Abstract: Purpose: Image guided radiotherapy (IGRT) strategies allow detecting and monitoring anatomical changes during external beam radiotherapy (EBRT). However, assessing the dosimetric impact of anatomical changes is not straightforward. In current IGRT strategies dose volume histograms (DVH) are not available due to lack of contours and dose recalculations on the cone-beam CT (CBCT) scan. This study investigates the feasibility of using automatically calculated DVH parameters in CBCTs using an independent dose calculation engine and propagated contours. Method: A prospective study (NCT03385031) of thirty-one breast cancer patients who received additional CBCT imaging (N = 70) was performed. Manual and automatically propagated contours were generated for all CBCTs and an automatic dose recalculation was performed. Differences between planned and CBCT-derived DVH parameters (mean and maximum dose to targets, 95% volume coverage to targets and mean heart dose (MHD)) were calculated using the dose verification system with manual and propagated contours and, in both cases, benchmarked against DVH differences quantified in the TPS using manually contoured CBCTs. Results: Differences in DVH parameters between the TPS and dose verification system with propagated contours were −1.3% to 0.7% (95% CI) for mean dose to the target volume, −0.3 to 0.2 Gy (95% CI) in MHD and −3.9% to 2.9% (95% CI) in target volume coverage. Conclusion: The use of an independent fully automatic dose verification system with contour propagation showed to be feasible and sufficiently reliable to recalculate CBCT based DVHs during breast EBRT. Volume coverage parameters, i.e. V95%, proved to be especially sensitive to contouring differences.